IMPLEMENTASI PERATURAN BUPATI BARITO TIMUR NOMOR 6 TAHUN 2015 TENTANG PENGADAAN BARANG/JASA DI DESA - Jhon Karigas; Irawanto Irawanto; Muhammad Jamili (Administraus, 2017)
Implementation of Barito Timur Regency’s RegulationNumber 6 year 2015 on Procurementof Goods / Services in the Village. Under the guidance of Mr. Irawanto as mentor I and Mr. M. Jamili As Supervisor II. The purpose of this research is to know the implementation of Regulation of Barito Timur Regent Number 6 Year 2015 concerning Procurement of Goods / Services in Village from Communication factor, Human Resources and Bureaucracy Structure but it will also give recommendation for Local Government in implementing Procurement of Goods / Services in Village East Barito Regency. The research method used is descriptive method with qualitative approach. Data collection was done by interview and documentation techniques. Triangulation technique is used to check the validity of research data. Data analysis in this research using steps Miles and Huberman is the process of analysis by using several components consisting of data reduction, presentation or display data and the conclusion / verification. The results showed that the Implementation of Barito Timur Regency’s RegulationNumber 6 year 2015 on Procurementof Goods / Services in the Village District Dusun East has not run optimally. Implementation still faces fundamental obstacles in communication is lack of socialization intensity done to executor of policy of procurement of goods / services in village. Another obstacle is the human resources, namely the low ability of procurement of goods / services in the village. While in the bureaucratic structure there has been no dispersion of responsibilities among the implementing Team for procurement of goods / services in the village. Implementasi Peraturan Bupati Barito Timur Nomor 6 Tahun 2015 tentang Pengadaan Barang/Jasa di Desa.Di Bawah Bimbingan Irawanto sebagai pembimbing I dan Muhammad Jamili Sebagai Pembimbing II. Tujuan penelitian ini adalah untuk mengetahui implementasi Peraturan Bupati Barito Timur Nomor 6 Tahun 2015 tentang Pengadaan Barang/Jasa di Desa dari faktor Komunikasi, Sumber Daya Manusia dan Struktur Birokrasi selain itu juga akan memberikan rekomendasi bagi Pemerintah Daerah dalam pelaksanaan Pengadaan Barang/Jasa di Desa di Kabupaten Barito Timur. Metode penelitian yang digunakan adalah metode deskriptif dengan pendekatan kualitatif. Pengumpulan data dilakukan dengan teknik wawancara dan dokumentasi. Teknik triangulasi digunakan untuk mengecek keabsahan data penelitian. Analisis data dalam penelitian ini menggunakan langkah-langkah Miles dan Huberman yaitu proses analisis dengan menggunakan beberapa komponen yang terdiri dari reduksi data, penyajian atau display data dan pengambilan kesimpulan/verifikasi. Hasil penelitian menunjukan bahwa implementasi Peraturan Bupati Barito Timur Nomor 6 Tahun 2015 tentang Pengadaan Barang/Jasa di Desa wilayah Kecamatan Dusun Timur belum berjalan optimal. Implementasi masih menghadapi hambatan yang mendasar dalam komunikasi yaitu kurangnya intesitas sosialisasi yang dilakukan kepada pelaksana kebijakan pengadaan barang/jasa di desa. Hambatan lainya adalah pada sumber daya manusia, yaitu rendahnya kemampuan pelaksana pengadaan barang/jasa di desa. Sementara pada struktur birokrasi belum ada penyebaran tanggung jawab diantara Tim pelaksana pengadaan barang/jasa di desa.